2019
DOI: 10.1007/s13197-019-03865-9
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of changes in rheological properties during processing of fermented cereal beverages

Abstract: Many indigenous fermented foods and beverages consumed throughout the world are produced at home or in crafts enterprises. The production of fermented beverages on a large commercial or industrial scale requires clearly established technical and technological requirements. This study shows a novel way to investigate the optimal process parameters of the Kyrgyz traditional fermented beverage Bozo using rotational rheological parameters. Five significant process parameters were investigated like cooking of mille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…Pearl millet when fermented for 48 h at an ambient temperature of 27-31°C and relative humidity of 72%-78% lead to an increase in the viscosity (843.33 to 849 cP) (Atuna et al, 2021) and similar results were also reported by Iskakova et al (2019) with P. miliaceum.…”
Section: Rheolog Ic Al Propertie Ssupporting
confidence: 77%
See 1 more Smart Citation
“…Pearl millet when fermented for 48 h at an ambient temperature of 27-31°C and relative humidity of 72%-78% lead to an increase in the viscosity (843.33 to 849 cP) (Atuna et al, 2021) and similar results were also reported by Iskakova et al (2019) with P. miliaceum.…”
Section: Rheolog Ic Al Propertie Ssupporting
confidence: 77%
“…Pearl millet when fermented for 48 h at an ambient temperature of 27–31°C and relative humidity of 72%–78% lead to an increase in the viscosity (843.33 to 849 cP) (Atuna et al, 2021) and similar results were also reported by Iskakova et al (2019) with P. miliaceum . Fermentation increased the viscosity linearly with the temperature as leaching of the amylose occurred from the swollen granules.…”
Section: Rheological Propertiessupporting
confidence: 74%
“…The fermentation of starchy sources is more complex compared to that of low molecular sugars (glucose or sucrose) because, in general, the starch must at first be converted into fermentable sugars. To achieve an almost complete starch degradation, two main types of amylolytic enzymes are required (α-amylase and glucoamylase) [98].…”
Section: Processing Technologies and Their Outcomementioning
confidence: 99%
“…Indeed, fermentation is one of the oldest and most economical methods to produce preserved food. In addition, fermented foods and beverages, containing lactic acid bacteria, are considered as probiotic products and they are of great significance for human health (Iskakova et al, 2019) and stingless bee pollen may be an excellent source.…”
Section: Sensorial Analysismentioning
confidence: 99%